Effect of caffeine intake on critical power model parameters determined on a cycle ergometer - Marcus Vinicius Machado; Alexandre Rosas Batista; Leandro Ricardo Altimari; Eduardo Bodnariuc Fontes; Ricardo Okada Triana; Alexandre Hideki Okano; Alessandro Custódio Marques; Orival Andries Júnior; Antonio Carlos de Moraes (Universidade Federal de Santa Catarina, 2010)
The aim of this study was to evaluate the effect of caffeine intake on critical power model parameters determined on a cycle ergometer. Eight male subjects participated in this study. A double-blind protocol consisting of the intake of pure caffeine (6 mg/kg) or placebo (maltodextrin) 60 min before testing was used. Subjects were submitted to four constant-load tests on a cycle ergometer. These tests were conducted randomly in the caffeine and placebo groups [checar] at intensities of 80, 90, 100 and 110% maximum power at a rate of 70 rpm until exhaustion to determine the critical power. As a criterion for stopping the test was adopted any rate fall without recovery by more than five seconds. The critical power and anaerobic work capacity were obtained by nonlinear regression and fitting of the curve to a hyperbolic power-time model. The Shapiro-Wilk test and paired Student t-test were used for statistical analysis. No significant differences in critical power were observed between the caffeine and placebo groups (192.9 ± 31.3 vs 197.7 ± 29.4 W, respectively). The anaerobic work capacity was significantly higher in the caffeine group (20.1 ± 5.2 vs 16.3 ± 4.2 W, p< 0.01). A high association (r2) was observed between the caffeine and placebo conditions (0.98 ± 0.02 and 0.99 ± 0.0, respectively). We conclude that caffeine intake did not improve critical power performance but increased anaerobic work capacity by influencing performance at loads of higher intensity and shorter duration.